Design, synthesis and biological evaluation of multifunctional tacrine-curcumin hybrids as new cholinesterase inhibitors with metal ions-chelating and neuroprotective property. Issue 8 (15th April 2017) - Liu, Zhikun; Fang, Lei; Zhang, Huan; Gou, Shaohua; Chen, Li
Graphical abstract: Abstract: Total sixteen tacrine-curcumin hybrid compounds were designed and synthesized for the purpose of searching for multifunctional anti-Alzheimer agents. In vitro studies showed that these hybrid compounds showed good cholinesterase inhibitory activity. Particularly, the potency of K3-2 is even beyond tacrine. Some of the compounds exhibited different selectivity on acetylcholinesterase or butyrylcholinesterase due to the structural difference. Thus, the structure and activity relationship is summarized and further discussed based on molecular modeling studies. The ORAC and MTT assays indicated that the hybrid compounds possessed pronounced antioxidant activity and could effectively protect PC12 cells from the H2 O2 /Aβ42-induced toxicity. Moreover, the hybrid compounds also showed positive metal ions-chelating ability in vitro, suggesting a potential to halt ion-induced Aβ aggregation. All the obtained results demonstrated that the tacrine-curcumin hybrid compounds, in particular compound K3-2, can be considered as potential therapeutic agents for Alzheimer's disease.